Descriptive Epidemiology of Homicides With Victim and Suspect Race or Hispanic Ethnicity Discordance in the United States: Analysis of National Violent Death Reporting System (NVDRS) 2005-2015. Issue 17 (September 2021) - Frankenfeld, Cara L.; Leslie, Timothy F.
Cross-racial violence is a high-profile issue in the United States; however, there is little empirical research on the epidemiology of cross-racial homicides. The objective of this work was to use national-level data to evaluate the characteristics of homicides in which the victim and suspect are of the same or different race or Hispanic ethnicity. Victims and suspects from National Violent Death Reporting System data (2005-2015) were classified into seven-categories on the basis of race/ethnicity (six non-Hispanic races or Hispanic ethnicity), and 51, 454 homicide events were classified as concordant (same race or ethnicity), discordant (different race or ethnicity), or unknown (missing race or ethnicity or no suspect information). While discordancy was observed to be similar across all race and ethnicity groups, it was less likely with relatives, romantic partners, and relatives of romantic partners; less likely to occur at home; less likely to occur in intimate partner violence–related homicides; less likely when the homicide was preceded by an argument over money or property; less likely when the homicide was associated with a family problem; more likely among rival gangs and strangers than other known person relationships; and more likely with drug-involved homicides. There were differences for victims of non-Hispanic Black race. Notably, discordance was more likely for justifiable self-defense and more likely with victim having used a weapon. These results suggest that discordant homicides may follow patterns of peer groups and close relationships in society regardless of victim race/ethnicity, that is, individuals may form closer relationships with individuals of the same race/ethnicity.